Postural Hypotension Associated with Nonelastic Pantyhose during Lymphedema Treatment - Jose Maria Pereira de Godoy; Daniel Zucchi Libanore; Maria de Fatima Guerreiro Godoy (Hindawi Limited, 2014)
The case of a 72-year-old female patient with elephantiasis is reported. The patient was submitted to two surgeries to remove the edema. After surgery, the leg again evolved to elephantiasis and eventually she was referred to the Clinica Godoy for clinical treatment. Intensive treatment was carried out (6 to 8 hours per day) and the patient lost more than 70% of the limb volume within one week. After this loss, the volume was maintained using grosgrain compression pantyhose for 24 hours per day. During the return appointment, the patient suffered from systemic hypotension (a drop of more than 30 mmHg within three minutes) while she was standing after removing the stocking. A further investigation showed that the symptoms only appeared when the stocking was worn for 24 hours. Thus, the patient was advised to use the stocking only during the day thereby avoiding the symptoms of hypotension.